Influence of Strategic Leadership on Generation Z Employees: A Strategic Approach to Organizational Performance - Kimonyo, Tabitha (European Journal of Business and Strategic Management, 2025)
Purpose: This study examines the impact of strategic leadership on Generation Z employees and explores how these leadership styles influence organizational performance. Generation Z, born between 1997 and 2012, brings distinct workplace expectations, including a desire for transparency, flexibility, and a meaningful work environment. Strategic leadership, with its focus on vision, adaptability, and informed decision-making, is crucial to harnessing Gen Z’s potential and fostering a culture of engagement, innovation, and productivity. Methodology: This study adopts a mixed-methods approach, collecting quantitative data through surveys and qualitative insights through interviews with Gen Z employees and strategic leaders across industries such as technology, finance, and healthcare. Findings: Results indicate that Gen Z responds positively to leadership styles that prioritize inclusivity, support open communication, and emphasize purpose-driven work. Leaders who actively promote innovation and involve employees in meaningful decision-making are particularly successful in engaging this cohort. Additionally, findings reveal that strategic leadership approaches tailored to Gen Z's values improve organizational outcomes, as evidenced by increased employee satisfaction, enhanced productivity, and reduced turnover rates. This study highlights the importance of adaptability in leadership strategies and suggests that aligning leadership practices with Gen Z’s preferences can significantly contribute to organizational performance. Unique Contribution to Theory, Practice and Policy: Recommendations include adopting flexible work models, encouraging ethical transparency, and creating career development opportunities, all of which cater to the unique motivations of Gen Z and build a foundation for sustained organizational success.